Advances in circularly polarized electroluminescence based on chiral TADF-active materials - Li, Meng; Chuan-Feng, Chen (Organic chemistry frontiers an international journal of organic chemistry, 2022)
Due to the promising application prospects of circularly polarized organic light-emitting diodes (CP-OLEDs) for future display and optoelectronic technology, especially in display screens, a variety of chiral luminescent materials, including chiral fluorescent polymers, chiral metal complexes, and chiral small organic molecules, have recently been developed for use as emitters for CP-OLEDs. Among reported chiral emitters, emerging chiral TADF-active materials are regarded as the most promising candidates for circularly polarized electroluminescence (CPEL) emitters because of their advantages of being metal free, easy derivatization and high device efficiency. In this review, we systematically summarize the development status and design strategies of chiral TADF-active materials with CPEL, covering chiral perturbed TADF molecules, intrinsically chiral TADF molecules, and TADF-sensitized fluorescent enantiomers. Additionally, the challenges and opportunities of promising TADF-based CPEL are also discussed.